A intervenção no lazer na política de segurança pública: a construção de saberes de oficineiros no programa Fica Vivo! - Samuel Santos (2013)
The professional of Physical Education works as a workshop teacher at Fica Vivo!, an action of Criminality Prevention and Social Politics of Estado de Minas Gerais and known as Citizen Public Security Politics. The Program focuses on young people between the ages of eleven and twenty four, who live in places that present a higher indicator of murder, in the city of Belo Horizonte, its surrounding cities, and the interior of the state of Minas Gerais. This work tries to identify and to analyze the construction of knowledge applied by workshop teachers, graduated in Physical Education, who work at Fica Vivo! in Belo Horizonte, as well as to understand how this knowledge is constructed and appropriated by them. Using a qualitative approach and a multi-methodological action, this study contains bibliographic, document, and field research. In the revision of this literature, studies about teachers knowledge, public security and leisure were used. During the document investigation, the following texts were selected and analyzed: Plano Estadual de Segurança Pública de Minas Gerais (2003), Metodologia do Programa Fica Vivo! (2009), and the institutional site of Secretaria de Estado de Defesa Social (SEDS), which has the responsibility to manage and to institutionalize the Program of actions. In the field research, an immersion in eleven workshops at Fica vivo! was made and the realization of nine semi-structured interviews with the workshop teachers responsible for the contents of sports and culture. The analysis of the interviews allowed the uprising of the following thematic categories: subject of research and construction of knowledge; knowledge used in the workshops; knowledge about the context of actuation; and relations between power and knowledge at Program Fica Vivo! The study shows how leisure is a central element during the construction of knowledge for workshop teachers and it has had a strong presence in political documents. Moreover, it can be seen as a social right, a citizenship instrument, and a social protection mechanism. The knowledge experiences of workshop teachers supply various tactics for the actuations. The research considers that the knowledge production needs to broaden the understanding of the different knowledge forms that can live side by side, scientific knowledge and the knowledge that appears from social and everyday cultural dynamics. Thus, opening possibilities for new dynamics of actuation on the populations and communities.